ENT530: Al-Matha'am Syed Corner / Muhammad Akram Hafeez Mahusain … [et al.] - Mahusain, Muhammad Akram Hafeez; Rosman, Muhammad Amirul Hafiz; Nooridzahir, Noor Syahirah; Hishamudin, Nurul Syazwina; Sudarmaji, Mas Izzati Massna (2019)
Al-Mutha'am Syed Corner is so called "Mamak Restaurant" that is located in Parit Buntar, Perak and owned by a local resident named, Encik Syed Azhar. This restaurant is the very first branch that owned by his father but it is organized by him itself and it has been open since 12 years ago. This restaurant has win a place in the heart of the residents. The owner also has open several branches in Klang Valley to extend their businesses. The branches has been re-branded with Nasi Kandar Express in Bandar Baru Bangi and Bandar Sri Putra, Bangi.